Comparison of MicroRNA Content in Plasma and Urine Indicates the Existence of a Transrenal Passage of Selected MicroRNAs - Pazourkova, Eva; Pospisilova, Sarka; Svobodova, Iveta; Horinek, Ales; Brisuda, Antonin; Soukup, Viktor; Hrbacek, Jan; Capoun, Otakar; Mares, Jaroslav; Hanus, Tomas; Babjuk, Marek; Korabecna, Marie (Advances in experimental medicine and biology, 2016)
MicroRNAs (miRNAs) in urine are examined as potential biomarkers. We examined the urine samples from 70 individuals (45 males, 25 females, mean age 65 years, range 20-84 years). Of the urine donors, 15 were healthy volunteers, 5 were patients with non-cancer diseases, 50 were patients with different stages of bladder cancer. To examine the spectrum of miRNAs in the cell-free fraction of urine, TaqMan Human miRNA Array Card A v.2.1 was used. A set of 30 miRNAs were found that are constantly present in urine supernatants independently of sex, age and health status of the subjects. We compared this set with miRNAs found in plasma, expressed in kidney and genito-urinary tract. Our results indicate that some miRNA could be transferred from the circulation into urine.
Keywords: senioři; senioři nad 80 let; nádory močového měchýře; regulace genové exprese u nádorů; mikro RNA; Middle Aged; mužské pohlaví; Transrenal passage of microRNAs; Urine supernatant; MicroRNA; Adult; mladý dospělý; MicroRNAs; Biomarkers, Tumor; polymerázová řetězová reakce s reverzní transkripcí; Aged, 80 and over; Young Adult; ženské pohlaví; nádorové biomarkery; Humans; Gene Expression Regulation, Neoplastic; ledviny; lidé středního věku; Reverse Transcriptase Polymerase Chain Reaction; Urinary Bladder Neoplasms; Genito-urinary tract; dospělí; Kidney; Female; Aged; Plasma; lidé; Male